Contemporaneity and entanglement: Archaeological site structure from a Bayesian perspective. (June 2020) - Parkington, John; Fisher, John W.; Hoyte, Simon; Lazarides, Maria; Woodborne, Stephan
Highlights: The shift from trying to assess the ages at death of archaeological seals from mandibles recovered from DFM and EBC results in a more persuasive assessment of the timing of seal deaths and site visits. This is because the seal months of death are not independent events but are entangled, that is related, when contemporaneity of materials, including the seal remains, is demonstrated. This is effectively a Bayesian approach to site structure. The seasonal implications of one seal mandible on that of others from the same camp visit, circumscribes the predicted month of death of all contemporary specimens. In shell middens that can be shown to be sets of diverse but contemporary food remains (shells, seals, hyraxes) and site features (hearths), this means that 'month(s) of site visit' are jointly defined by different sets of evidence. At DFM, this results in a tighter reflection of seasonality of site visit and at EBC shows different predicted site visits from Late Holocene and Terminal Pleistocene levels. Abstract: Previously we (Woodborne et al., 1995) and many others have attempted to pinpoint the seasonality of hunter gatherer site visits by assessing the 'ages at death' of animals with a restricted birth season. We used seal remains from two late Holocene sites along the Cape west coast. In this reevaluation, including larger samples of both modern and archaeological seal bones, we rephrase the question from 'at what age did this seal (these seals) die'? to 'which month or months most effectively characterize the likely capture (death) date for this set of seals'? By shifting focus from 'age at death' to 'month of death' we attempt a more Bayesian approach by using contemporaneity of linked seal deaths at sites as a form of prior knowledge to inform predictions of season of visit. We also illustrate the entanglement of radiocarbon samples, shellfish remains, refitted ostrich eggshell water flasks, hearths and seal mandibles in the layout of the DFM site. Reflections of the brevity of occupation at DFM and the entanglement of observations are assembled to support the notion of contemporaneity of seal deaths there.